2017
DOI: 10.19082/4985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the shear bond strength of self-adhesive resin cements to enamel and dentin with different protocol of application

Abstract: AimThe aim of the present study was to determine the shear bond strength of self-adhesive resin cements to enamel and dentin with and without surface treatments, and compare them with conventional resin cement as the control group.MethodsIn this experimental study, buccal and lingual surface of the thirty sound human premolars were polished in order to obtain a flat surface of enamel (E) in buccal, and dentin (D) in lingual. Sixty feldspathic ceramic blocks (2×3×3 mm) were prepared and randomly divided into si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Regarding enamel substrate conditioning, Moghaddas et al . ( 4 ) mentioned that there is no influence on the strength of the union. However, for the dentin substrate, it is argued that the self-adhesive cement is not able to demineralize/dissolve the smear layer completely.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding enamel substrate conditioning, Moghaddas et al . ( 4 ) mentioned that there is no influence on the strength of the union. However, for the dentin substrate, it is argued that the self-adhesive cement is not able to demineralize/dissolve the smear layer completely.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the dentin substrate, it is argued that the self-adhesive cement is not able to demineralize/dissolve the smear layer completely. And this partial demineralization of the smear layer results in a lower potential for adhesion to dentin ( 4 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to dentin, some studies showed that the performance of self-adhesive resin cements is comparable to that of etch-and-rinse systems on coronal dentin. Comparison of the shear bond strength of self-adhesive resin cements to enamel and dentin with different protocol of application ( Moghaddas et al 2017 ). Rodrigues et al (2015) , while other studies showed opposite results, the bond strength to dentin with self-adhesive cements being significantly lower ( De Angelis et al, 2011 ; Lührs et al, 2010 ; Viotti et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second approach is through using self-adhesive resin cements which do not need any preceding intervention applied to the tooth. They are composed of multifunctional acid methacrylate, the acidic content causes demineralization of dentin, while the methacrylate component(resin) infiltrates dentin forming hybrid layer and resin tags, with the smear layer incorporated in the hybrid layer (Moghaddas et al 2017).…”
Section: Introductionmentioning
confidence: 99%